Standard precautions: knowledge and practice among nursing and medical students in a teaching hospital in Brazil - Garcia-Zapata, Mary Rocha-Carneiro; Silva e Souza, Adenícia Custódia; Valadares Guimarães, Janaína; Veiga Tipple, Anaclara Ferreira; Aparecida Prado, Marinésia; García-Zapata, Marco Tulio Antonio (International Journal of Infection Control, 2009)
Compliance with standard precautions measures is essential to prevent and control healthcare-associated infections. The objective of the study was to evaluate the knowledge and practice of hand washing, use of gloves and the handling and disposal of needlesticks and other sharp objects among nursing and medical students. This is a descriptive observational study, which used a questionnaire and a check list. Knowledge of standard precaution measures was evaluated in 48/48 (100.0%) nursing students and 93/112 (83.0%) medical students. At the teaching hospital, 26/37 (70.3%) nursing students and 78/93 (83.9%) medical students belonging to the population being investigated were observed during their clinical practice. These results were compared intra groups. Knowledge of hand hygiene procedures was higher than what was observed in the clinical practice in both groups of students, (X²; p≤0.001). Compliance with the use of sterile and non-sterile gloves, and handling and disposal of needlesticks and other sharp objects was higher than the knowledge of these procedures among nursing students, and a statistically significant difference was observed with regards to sterile glove usage (X²; p=0.009). Regarding medical students, there was no statistical difference between knowledge and practice insofar as these two types of gloves were concerned, as well as regarding the handling and disposal of needlesticks and other sharp objects. Performance of both groups in terms of knowledge of hand hygiene showed a dichotomy between the teaching and the practice of these standard precautions. Results have shown a deficiency in the teaching-learning process for the other measures evaluated.